Characterization of Dissolved Organic Matter in River Water by Conventional Methods and Direct Sample Analysis-Time of Flight-Mass Spectrometry - T. Garrido Reyes; J. Mendoza Crisosto (Journal of Chemistry)
The dissolved organic matter in surface waters is composed of fractions of different molecular weight and polarity, characteristics that determine their capacity for complexing different types of pollutants and their environmental impact. In this study, the dissolved organic matter in the surface water of the Bio-Bio River (Central Region of Chile) was characterized chemically and spectroscopically after fractionating by molecular weight and polarity. The technique of direct sample analysis-time of flight-mass spectrometry (DSA-TOF-MS) was used to obtain more information on the composition of dissolved organic matter. It is concluded that dissolved organic matter found in the water of the river from the site of minor human impact (Rucalhue) has a predominantly natural origin, with a high content of aromatic carbon, in contrast to dissolved organic matter found in the waters of the sites that have higher human impact (Laja and Concepción), characterized by a greater molecular size and higher organic carbon content. These results are consistent with those obtained from DSA-TOF-MS, where higher correlation was observed between the mass spectrum of the standard commercial humic acid and dissolved organic matter found in the sectors of Laja and Concepción, unlike the spectrum mass of lignin which is more like dissolved organic matter found in the sector Rucalhue.